Insight Into the Relation Between Nutritional Benefits of Aquaculture Products and its Consumption Hazards: A Global Viewpoint - Arshad, Naufal; Samat, Narimah; Lee, Lai Kuan (Frontiers in Marine Science, 2022)
Aquaculture is playing huge roles in supporting the needs and demands of the fish and other aquatic organism globally. Being a vital contributor in fisheries sector, aquatic source derived from the aquaculture industry is well-known for its high nutritive values that are compromised with high quality protein, essential omega-3 fatty acids, vitamins and minerals. Aquaculture has also widen fish availability to regions and countries with limited access to the farmed species, leading to improved nutrition and food security. However, the presence of dangerous contaminants, notably the heavy metals, endocrine disrupting compounds, polycyclic aromatic hydrocarbons, microplastics as well as antimicrobial drug residues have been detected in the aquaculture products. In conjunction, risk-benefit assessment (RBA) approach has been proposed to be used as meaningful tool for the evaluation of health impacts of the aquatic sources consumption towards the targeted population. This narrative review outlines a compilation of aquaculture products as a nutritional source for human consumption. The aquaculture industry are well-appreciated, especially in the low-income countries for achieving sustainable food security. The organoleptic and preferences of aquaculture products as means of dietary variations were demonstrated. The detrimental contaminants contained in the commercially available aquaculture products were quantitatively outlined. Furthermore, the adaptation of risk benefit approach underlying its potent impacts on public health concern, together with its current challenges and limitations, are elucidated.